PROPHYLACTICS OF IODINE DEFICIENCY DISEASES - L.S. Namazova; I.V. Shirokova (Union of pediatricians of Russia, 2008)
This article covers a relevant problem of modern medicine - that of iodine deficiency, which results in derangement of all vital process in the body, decreasing the intellectual and physical development of a child. Taking into account the incidence of this condition, prophylactics of iodine deficiency becomes a national objective. Authors suggest possible ways to make up for iodine deficiency in the body.Key words: iodine deficiency, thyroid hormones, potassiumiodide, children.